Prolixan® : anti-inflammatory - antirheumatic agent (Alkaloida chemical factory, 1978)
The booklet focuses on Prolixan, a non-steroidal anti-inflammatory agent used to treat rheumatic diseases. Intended for professional public.
Keywords: Antirheumatic Agents; antirevmatika; farmacie a farmakologie; azapropazon; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; revmatologie; Apazone; Prolixan